Influencing factors related to stroke patients’ rehabilitation motivation: a scoping review - Fan, Xiaowen; Xia, Yi; Wu, Junrong; Jia, Shulei; Hu, Jiangyu (Frontiers in Neurology, 2025)
Mounting epidemiological evidence indicates a rising global prevalence of stroke among adults and older populations, often leading to severe functional impairments that compromise daily living. While rehabilitation exercise is recognized as a safe and effective strategy for functional recovery, inadequate rehabilitation motivation frequently undermines therapeutic efficacy. Exercise adherence plays a critical role in mitigating physical disability and mortality rates, yet current research lacks systematic insights into influencing of patient rehabilitation motivation. This scoping review synthesizes evidence from 23 studies across domestic and international databases to identify multidimensional factors influencing post-stroke rehabilitation motivation. Key influencing include intrinsic drivers (e.g., self-efficacy, depression), extrinsic supports (familial or social support, economic burden), disease-specific characteristics (severity, functional deficits), and intervention strategies (cognitive-behavioral therapy, gamified rehabilitation). Findings highlight the necessity of integrating personalized motivational assessments into clinical protocols and developing interdisciplinary interventions to address motivational barriers. These insights provide a foundation for optimizing rehabilitation frameworks and improving long-term patient outcomes.